Involvement of Metabolic Lipid Mediators in the Regulation of Apoptosis - Piotr Wójcik; Neven Žarković; Agnieszka Gęgotek; Elżbieta Skrzydlewska (Biomolecules, 2020)
Apoptosis is the physiological mechanism of cell death and can be modulated by endogenous and exogenous factors, including stress and metabolic alterations. Reactive oxygen species (ROS), as well as ROS-dependent lipid peroxidation products (including isoprostanes and reactive aldehydes including 4-hydroxynonenal) are proapoptotic factors. These mediators can activate apoptosis via mitochondrial-, receptor-, or ER stress-dependent pathways. Phospholipid metabolism is also an essential regulator of apoptosis, producing the proapoptotic prostaglandins of the PGD and PGJ series, as well as the antiapoptotic prostaglandins of the PGE series, but also 12-HETE and 20-HETE. The effect of endocannabinoids and phytocannabinoids on apoptosis depends on cell type-specific differences. Cells where cannabinoid receptor type 1 (CB1) is the dominant cannabinoid receptor, as well as cells with high cyclooxygenase (COX) activity, undergo apoptosis after the administration of cannabinoids. In contrast, in cells where CB2 receptors dominate, and cells with low COX activity, cannabinoids act in a cytoprotective manner. Therefore, cell type-specific differences in the pro- and antiapoptotic effects of lipids and their (oxidative) products might reveal new options for differential bioanalysis between normal, functional, and degenerating or malignant cells, and better integrative biomedical treatments of major stress-associated diseases.